PtCu3, PtCu and Pt3Cu Alloy Nanoparticle Electrocatalysts for Oxygen Reduction Reaction in Alkaline and Acidic Media - Oezaslan, Mehtap; Hasché, Frédéric; Strasser, Peter (Journal of the Electrochemical Society, 2012)
Dealloying of Pt bimetallic nanoparticles is a promising synthesis method to prepare highly active electrocatalysts for oxygen reduction reaction (ORR) in alkaline and acidic PEM fuel cells. We present here a structural, compositional and electrochemical characterization linked with ORR activity for carbon supported PtCu3, PtCu, and Pt3Cu alloy nanoparticles in different electrolytes and pH values. The effects of electrolyte and pH are systematically examined on the ECSA and Pt mass based activity (jmass) for various Pt-Cu alloys. We observed the formation of Cu oxide species and redissolution/redeposition of Cu species during the voltage cycling up to 1.0 V/RHE in 0.1 M KOH. In contrast, the voltage cycling in 0.1 M HClO4 immediately causes the dissolution of Cu and results in Pt-enriched particle surface. We have correlated the ECSA and mass activity with the as-synthesized composition in dependence on both electrolytes. In summary, after voltage cycling in 0.1 M HClO4 the values of jmass increase according: Pt3Cu < PtCu < PtCu3. However, after voltage cycling in 0.1 M KOH the values of jmass increase in the following trend: PtCu3 < PtCu < Pt3Cu. Only after activation process, PtCu3 core-shell catalyst shows significantly enhanced ORR activity in 0.1 M KOH compared to pure Pt.